Corporate social responsibility engagement by companies: Theory, concept, model, and impact - Rusnah, Muhamad; Noor Akma, Mohd Salleh; Mohd Sabrun, Ibrahim (Routledge, 2019)
Engaging in corporate social responsibility (CSR) should be a deliberate decision by companies. Undeniably, engaging in CSR brings multiple benefits to companies; however, the social and environmental actions that businesses engage in are also bound to bring advantages to society. This chapter aims to describe the corporate social responsibility in business, and investigate some theoretical approaches to CSR engagement, as well as the concepts and models. The goal is to examine the theoretical foundations of CSR, the stakeholder theory and legitimacy theory, and how these two foundations translate into economic sustainability. We start by presenting these two theoretical foundations, then defining the CSR concepts and the generic CSR models. Lastly, the chapter discusses the impact of CSR engagement by companies from the viewpoint of the theoretical foundation, concepts, and model.